Effects of Hanwoo (Korean cattle) manure as organic fertilizer on plant growth, feed quality, and soil bacterial community - Lee, Junkyung; Jo, Na-Yeon; Shim, Su-Yeon; Linh, Le Tran Yen; Kim, Soo-Ryang; Lee, Myung-Gyu; Hwang, Sun-Goo (Frontiers in Plant Science, 2023)
The development of organic manure from livestock excreta is a useful source for sustainable crop production in environment-friendly agriculture. Organic manure increases soil microbial activity and organic matter (OM) supply. The excessive use of chemical fertilizers (CFs) leads to air and water pollution caused by toxic chemicals and gases, and soil quality degradation via nutrient imbalance due to supplying specific chemical components. Thus, the use of organic manure will serve as a long-term supply of various nutrients in soil via OM decomposition reaction as well as the maintenance of environment. In this study, we aimed to analyze the diverse effects of Hanwoo manure (HM) on plant growth, feed quality, and soil bacterial communities in comparison with CFs, commercial poultry manure (CM), and the combined use of chemical fertilizer and Hanwoo manure (HM+CF). We analyzed the contents of crude matter (protein, fat, fiber, and ash), P, acid detergent fiber (ADF), and neutral detergent fiber (NDF) through feed quality analysis, and the contents or activities of total phenol, total flavonoid, ABTS, nitrite scavenging, and reducing power via the antioxidant assay. Furthermore, the soil microbial communities were determined using 16S rRNA sequencing. We compared the soil bacteria among different soil samples by using amplicon sequence variant (ASV) analysis. We observed increased OM in the soil of the HM group compared to that of the CF and non-treated groups over a period of two years. Moreover, HM+CF treatment enormously improved plant growth. Organic manure, especially HM, caused an increase in the content of crude ash and phosphorus in plants. There were no significant differences in total polyphenol, total flavonoid, ABTS, nitrite scavenging, and reducing power in plants between HM and CF groups. Finally, we detected 13 soil bacteria (Acidibacter, Algisphaera, Cystobacter, Microvirga, Ohtaekwangia, Panacagrimonas, Pseudarthrobacter, Reryanella, Rhodoligotrophos, Solirubrobacter, Stenotrophobacter, Tellurimicrobium, and Thermomarinilinea) that were considerably correlated with OM and available phosphorus, and three considerably correlated bacteria were specifically distributed in CF or organic manure. The results suggest that HM is a valuable source of organic manure that can replace CF for sustainable crop production.